2020
DOI: 10.1177/0003134820972083
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Complete Response Following Neoadjuvant Therapy for Gastric Adenocarcinoma: A National Cancer Database Analysis on Incidence, Predictors, and Outcomes

Abstract: Introduction With advances in multimodal therapy, survival rates in gastric cancer have significantly improved over the last two decades. Neoadjuvant therapy increases the likelihood of achieving negative margins and may even lead to pathologic complete response (pCR). However, the impact of pCR on survival in gastric cancer has been poorly described. We analyzed the rate and predictors of pCR in patients receiving neoadjuvant therapy as well as impact of pCR on survival. Methods We conducted a National Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…Finally, response to preoperative chemotherapy has been shown to have prognostic value in patients with breast and rectal cancer, with patients achieving pathologic complete response (pCR) enjoying longer disease-free survival (DFS)[ 22 ]. Newer retrospective data also suggested a similar pattern for gastric and GEJ cancer[ 23 , 24 ], while results from the prospective trials cited below showed a trend for improved outcomes in patients achieving complete response in preoperative therapy.…”
Section: Treatmentmentioning
confidence: 84%
“…Finally, response to preoperative chemotherapy has been shown to have prognostic value in patients with breast and rectal cancer, with patients achieving pathologic complete response (pCR) enjoying longer disease-free survival (DFS)[ 22 ]. Newer retrospective data also suggested a similar pattern for gastric and GEJ cancer[ 23 , 24 ], while results from the prospective trials cited below showed a trend for improved outcomes in patients achieving complete response in preoperative therapy.…”
Section: Treatmentmentioning
confidence: 84%
“… 29 Retrospective studies comparing nCRT with nCT for gastric cancers, specifically, found similar data regarding improved pCR rates of nCRT compared with nCT, but there were no statistically significant improvements in OS. 30 , 31 The phase III Neoadjuvant Trial in Adenocarcinoma of the Esophagus and Esophago-Gastric Junction International Study (Neo-AEGIS) 32 comparing neoadjuvant carboplatin-paclitaxel plus radiation therapy (CROSS) with perioperative chemotherapy (ie, the MAGIC regimen or FLOT) for locally advanced esophageal and esophago-gastric junction (AEG) cancers is ongoing, and preliminary results found significant differences in pCR for CROSS vs MAGIC-FLOT (16% vs 5%, respectively) but similar 3-year survival rates (56%; 95% CI, 47%-64% vs 57%; 95% CI, 48%-65%). Although this trial examined AEG and esophageal cancers, it begs the question whether pCR is an adequate estimator associated with improved survival for gastric cancer and suggests that perioperative chemotherapy is noninferior to nCRT.…”
Section: Discussionmentioning
confidence: 99%
“…However, the POET trial was limited to patients with cancers of the lower esophagus and gastric cardia; therefore, it is unclear how this can be extrapolated to all gastric cancers . Retrospective studies comparing nCRT with nCT for gastric cancers, specifically, found similar data regarding improved pCR rates of nCRT compared with nCT, but there were no statistically significant improvements in OS . The phase III Neoadjuvant Trial in Adenocarcinoma of the Esophagus and Esophago-Gastric Junction International Study (Neo-AEGIS) comparing neoadjuvant carboplatin-paclitaxel plus radiation therapy (CROSS) with perioperative chemotherapy (ie, the MAGIC regimen or FLOT) for locally advanced esophageal and esophago-gastric junction (AEG) cancers is ongoing, and preliminary results found significant differences in pCR for CROSS vs MAGIC-FLOT (16% vs 5%, respectively) but similar 3-year survival rates (56%; 95% CI, 47%-64% vs 57%; 95% CI, 48%-65%).…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical practice has transitioned toward neoadjuvant therapy as the standard of care in gastric cancer for the purpose of downstaging disease, especially those with clinical T3, T4, and node‐positive disease, and ensuring delivery of an adequate total dose of systemic therapy, pathologic complete response to therapy remains limited, estimated at 3%–15%% 11 . This lends to a higher local and distant recurrence rate, ultimately influencing survival 12 .…”
Section: Adjuvant Therapy For Resected Gastric Cancermentioning
confidence: 99%